Beyond White Gum Valley: Knutsford - Integrating energy, water and built form solutions in an urban regeneration and infill precinct. - Mouritz, Mike; Galloway, David; London, Geoffrey; Todoronvic, Tatjana (2019)
Beyond WGV set out to investigate site specific scenarios for sustainable infill at the Knutsford Precinct (which incorporates the Knutsford and Swanbourne Structure Plan areas) in the City of Fremantle. The emphasis has been on identifying ways to enabling distributed district scale infrastructure to deliver low carbon and resilient development, particularly the possibility of community battery storage. The aim was also explore the potential for distributed water infrastructure scenarios through a proposed partnership with the CRC for Water Sensitive Cities.